2008
DOI: 10.4025/actascianimsci.v30i1.3607
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de inclusão do resíduo do milho (mazoferm), em substituição ao farelo de soja para vacas em lactação

Abstract: Níveis de inclusão do resíduo do milho (mazoferm) Níveis de inclusão do resíduo do milho (mazoferm) Níveis de inclusão do resíduo do milho (mazoferm) Níveis de inclusão do resíduo do milho (mazoferm), , , , em substituição em substituição em substituição em substituição ao farelo de soja para vacas em lactação ao farelo de soja para vacas em lactação ao farelo de soja para vacas em lactação ao farelo de soja para vacas em lactação

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Silva et al (2008) found no treatment effect on milk yield for animals that consumed corn steep liquor, but these authors worked with a daily milk yield of 14.22 kg, which corresponds to animals that require low-quality diets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silva et al (2008) found no treatment effect on milk yield for animals that consumed corn steep liquor, but these authors worked with a daily milk yield of 14.22 kg, which corresponds to animals that require low-quality diets.…”
Section: Resultsmentioning
confidence: 99%
“…A linear decrease in the dry matter intake (DMI) was observed by Silva et al (2008), who replaced five dietary corn steep liquor levels (0.0, 3.5, 7.0, 10.5 and 14.0%) with soybean meal in the diet of lactating cows yielding 15 kg/d of milk. This finding can be attributed to the bitter taste of the product, i.e., the psychogenic factor.…”
Section: Resultsmentioning
confidence: 99%
“…Using crossbred (¾ Holstein x Gyr) cows with an average milk production of 15 kg/day, Silva et al (2008) found no effects on daily milk production or the fat content of the milk when soybean meal was replaced with maize steep liquor. However, for high-producing cows (25 kg milk/day), Santos et al (2012) reported a reduction in daily milk production without affecting the fat content.…”
Section: Introductionmentioning
confidence: 92%
“…However, soybean meal is an expensive commodity that increases the cost of animal production. To solve these problems, studies have been conducted with alternative feeds to examine the effects of partial or total replacement of soybean meal in diets (Irshaid & Harb, 2003;Titi, 2003;Haddad, 2006;Silva et al, 2008;Santos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation